A construção do conhecimento pela análise de inteligência na Crise dos Mísseis de Cuba - Rodrigo Fileto Cuerci Maciel (2013)
This present research investigates the practice of intelligence analysis, which consists of the construction of knowledge related to any player who can possibly be acting against the State. For such, the intelligence analysis in the United States of America was approached as a means to understand its major characteristics. The present work found that intelligence analysis in the U.S. has based its methods on the positivist parameters of science. Therefore, to better understand how it functions nowadays, intelligence analysis was studied according to the parameters of scientific epistemology. Thus, the development of the U.S intelligence analysis practiced during the Cuban Missile Crisis in 1962 was investigated in order to reconstruct the procedures of collection and analysis of information, and also to verify whether beliefs and assumptions affected analytical production. As a result, it was noted that the positivist conception of science determined that every piece of information should be first processed and only then sent to the personnel in charge of strategic analysis. Such procedures delayed the information flow. Likewise, the positivist conception blocked the formulation of new hypotheses throughout the event. Moreover, beliefs and assumptions were actually present and affected analytical production. However, they were neither made explicit nor questioned because the theoretical formulation of intelligence analysis advocated that the analyst must not be influenced by beliefs or assumptions.